Highly photostable near-infrared fluorescent pH indicators and sensors based on BF2-chelated tetraarylazadipyrromethene dyes - Borisov, Sergey M. (2013)
In this study, a series of new BF2-chelated tetraarylazadipyrromethane dyes are synthesized and are shown to be suitable for the preparation of on/off photoinduced electron transfer modulated fluorescent sensors. The new indicators are noncovalently entrapped in polyurethane hydrogel D4 and feature absorption maxima in the range 660–710 nm and fluorescence emission maxima at 680–740 nm. Indicators have high molar absorption coefficients of 80 000 M–1 cm–1, good quantum yields (up to 20%), excellent photostability and low cross-sensitivity to the ionic strength. pKa values of indicators are determined from absorbance and fluorescence measurements and range from 7 to 11, depending on the substitution pattern of electron-donating and -withdrawing functionalities. Therefore, the new indicators are suitable for exploitation and adaptation in a diverse range of analytical applications. Apparent pKa values in sensor films derived from fluorescence data show 0.5–1 pH units lower values in comparison with those derived from the absorption data due to Förster resonance energy transfer from protonated to deprotonated form. A dual-lifetime referenced sensor is prepared, and application for monitoring of pH in corals is demonstrated.